2016
DOI: 10.1021/acsbiomaterials.6b00419
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Hydrogel Properties to Promote the Assembly of Salivary Gland Spheroids in 3D

Abstract: Current treatments for chronic xerostomia, or “dry mouth”, do not offer long-term therapeutic benefits for head and neck cancer survivors previously treated with curative radiation. Towards the goal of creating tissue-engineered constructs for the restoration of salivary gland functions, we developed new hyaluronic acid (HA)-based hydrogels using thiolated HA (HA-SH) and acrylated HA (HA-AES) with a significant molecular weight mismatch. Four hydrogel formulations with varying HA concentration, (1–2.4 wt%) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 44 publications
2
63
0
Order By: Relevance
“…[12] Our custom-designed HA hydrogels promoted spheroid assembly from dispersed hS/PCs. [14] We further discovered that hS/PCs cultured in HA gels decorated with bioactive peptides expressed a significantly higher levels of progenitor markers as compared to the unmodified HA gels. [12] The current study aimed to create physiologically relevant microtissues composed of myoepithelial cells and organized, acini-like spheroids to replicate the function of intact acini-hSMEC assemblies in tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[12] Our custom-designed HA hydrogels promoted spheroid assembly from dispersed hS/PCs. [14] We further discovered that hS/PCs cultured in HA gels decorated with bioactive peptides expressed a significantly higher levels of progenitor markers as compared to the unmodified HA gels. [12] The current study aimed to create physiologically relevant microtissues composed of myoepithelial cells and organized, acini-like spheroids to replicate the function of intact acini-hSMEC assemblies in tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Custom-designed HA hydrogels have shown success in maintaining high viability of single hS/PCs and promoting the formation of spheroid structures in vitro . [13, 14] In this study, we utilized PEGDMI to crosslink HA-SH as rapid gelation is necessary to prevent the microtissue assemblies from settling. Our initial experiments showed that hSMECs remained on the outer surface of the hS/PC spheroids for up to 48 h in the HA gel without any biological signals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells in these structures formed cell-cell junctions, secreted basement membrane proteins and maintained key stem/progenitor markers. 132 Thus, incorporation of time-dependent, dynamic features into a covalently cross-linked HA network produces an adaptable hydrogel framework that promotes hS/PC assembly and supports early aspects of tissue morphogenesis.…”
Section: Chemical Approaches To Hydrogel Synthesismentioning
confidence: 99%